Cathode active material precursor and method of preparing the same

KR103036554B1Active Publication Date: 2026-10-21POSCO FUTURE M CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
KR1020240115215
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2026-10-21
Estimated Expiration
2044-08-27

Smart Images

  • Figure 112024093776169-PAT00002_ABST
    Figure 112024093776169-PAT00002_ABST
Patent Text Reader

Abstract

The positive electrode active material precursor for a lithium secondary battery according to the present invention comprises a transition metal precursor that includes nickel and manganese but does not include cobalt, and the transition metal precursor comprises secondary particles formed by the aggregation of primary particles, and the transition metal precursor comprises pores having a bimodal distribution in which two peaks appear at pore diameters in the range of 1 nm to 20 nm in a pore size distribution graph obtained through the BJH (Barrett-Joyner-Halenda) method.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a positive electrode active material precursor and a method for manufacturing the same. Background Technology

[0002] With the recent rapid proliferation of battery-powered electronic devices such as mobile phones, laptop computers, and electric vehicles, the demand for small, lightweight, and relatively high-capacity rechargeable batteries is increasing rapidly. In particular, lithium-ion batteries are gaining prominence as power sources for portable devices due to their lightweight nature and high energy density. Consequently, research and development aimed at improving the performance of lithium-ion batteries is actively underway.

[0003] Furthermore, as interest in environmental issues grows, there is increasing interest in electric vehicles and hybrid electric vehicles that can replace fossil fuel-using vehicles, such as gasoline and diesel cars, which are one of the major causes of air pollution. Consequently, active research is underway to utilize lithium-ion batteries as a power source for electric and hybrid electric vehicles. Lithium-ion batteries generally consist of a cathode containing a positive active material, a negative electrode containing a negative active material, a separator, and an electrolyte, and charging and discharging are performed through the intercalation and decalation of lithium ions. Since these lithium-ion batteries possess advantages such as high energy density, high electromotive force, and the ability to deliver high capacity, they are being applied in various fields.

[0004] In addition, research is actively underway to improve structural stability and suppress interfacial degradation during charging and discharging in lithium secondary batteries. For example, to enhance electrochemical properties in existing NCM and NCA-based active materials, cathode active materials have primarily been manufactured by incorporating cobalt during the precursor and sintering stages. Furthermore, research is actively being conducted to ensure stability by applying techniques such as additional coating and doping to improve structural stability and suppress interfacial degradation that occurs during charging and discharging. Additionally, in the case of NM-based active materials containing only Ni and Mn, research is also actively being conducted because the absence of Co offers cost-saving benefits. The problem to be solved

[0005] The present invention aims to provide a positive electrode active material precursor capable of improving the room temperature discharge capacity of the positive electrode active material.

[0006] In addition, the present invention aims to provide a method for manufacturing a positive electrode active material precursor that can improve the room temperature discharge capacity of the positive electrode active material. means of solving the problem

[0007] A positive electrode active material precursor according to one embodiment of the present invention comprises a transition metal precursor comprising nickel and manganese but not cobalt, wherein the transition metal precursor comprises secondary particles formed by the aggregation of primary particles, and wherein the transition metal precursor comprises pores having a bimodal distribution in which two peaks appear at pore diameters in the range of 1 nm to 20 nm in a pore size distribution graph obtained through the BJH (Barrett-Joyner-Halenda) method.

[0008] In the above pore size distribution graph, one peak may be located at a pore diameter of less than 10 nm, and another peak may be located at a pore diameter greater than 10 nm.

[0009] The pore volume of the transition metal precursor calculated from the pore size distribution graph above is 0.1 cm 3 / g to 0.12 cm 3 It can be / g.

[0010] The above transition metal precursor may include NiMnO3.

[0011] In the XRD pattern of the above transition metal oxide, the full width at half maximum (FWHM) of the XRD peak (2θ = 41° to 43°) for the (113) crystal plane of NiMnO3 may be in the range of 1.2° to 1.6°.

[0012] The above transition metal precursor may contain 55 mol% to 80 mol% of manganese among the total transition metals.

[0013] The above transition metal precursor is 35 m 2 / g to 42 m 2 / It can have a BET specific surface area of ​​g.

[0014] A method for manufacturing a cathode active material precursor according to another aspect of the present invention comprises the steps of: co-precipitating nickel raw material and manganese raw material to produce a transition metal precursor that does not contain cobalt; and heat-treating the transition metal precursor at 350°C to 450°C for 3 to 7 hours, wherein the heat-treating step may be performed in an air atmosphere in which the carbon dioxide content is in the range of 0.01 to 100 weight ppm.

[0015] The heat-treated transition metal precursor comprises secondary particles formed by the aggregation of primary particles, and the heat-treated transition metal precursor comprises pores having a bimodal distribution in pore diameters ranging from 0.1 nm to 20 nm in a pore size distribution graph obtained through the BJH (Barrett-Joyner-Halenda) method.

[0016] The pore volume of the transition metal precursor calculated from the above pore size distribution graph is 0.1 cm 3 / g to 0.12 cm 3 It can be / g.

[0017] The heat-treated transition metal precursor may include NiMnO3.

[0018] In the XDR pattern of the heat-treated transition metal oxide, the full width at half maximum (FWHM) of the XRD peak (2θ = 41° to 43°) for the (113) crystal plane of NiMnO3 may be in the range of 1.2° to 1.6°.

[0019] The above transition metal precursor may contain 55 mol% to 80 mol% of manganese among the total transition metals.

[0020] The heat-treated transition metal precursor is 35 m 2 / g to 42 m 2 / It can have a BET specific surface area of ​​g. Effects of the invention

[0021] The positive electrode active material precursor for a lithium secondary battery according to the present invention has pores with a pore diameter of 20 nm or less having a bimodal distribution and has a high pore volume, thereby improving the room temperature discharge capacity of the positive electrode active material for a lithium secondary battery.

[0022] In addition, the method for manufacturing a positive electrode active material precursor for a lithium secondary battery according to the present invention can improve the room temperature discharge capacity of the positive electrode active material for a lithium secondary battery by having a high pore volume and pores with a pore diameter of 20 nm or less that have a bimodal distribution. Brief explanation of the drawing

[0023] Figure 1 shows X-ray diffraction patterns of a positive electrode active material precursor for a lithium secondary battery prepared according to the embodiments and comparative examples of the present invention. FIG. 2 shows the pore size distribution of a positive electrode active material precursor for a lithium secondary battery prepared according to the embodiments and comparative examples of the present invention. Specific details for implementing the invention

[0024] In this specification, terms such as first, second, and third are used to describe various parts, components, regions, layers, and / or sections, but are not limited thereto. These terms are used solely to distinguish one part, component, region, layer, or section from another part, component, region, layer, or section. Accordingly, the first part, component, region, layer, or section described below may be referred to as the second part, component, region, layer, or section without departing from the scope of the invention.

[0025] The technical terms used herein are for the reference of specific embodiments only and are not intended to limit the invention. The singular forms used herein include plural forms unless phrases clearly indicate otherwise. As used in the specification, the meaning of "comprising" specifies certain characteristics, areas, integers, steps, actions, elements, and / or components, and does not exclude the presence or addition of other characteristics, areas, integers, steps, actions, elements, and / or components.

[0026] When it is stated that one part is "above" or "on" another part, it may be directly above or on the other part, or other parts may be involved in between. In contrast, when it is stated that one part is "directly above" another part, no other parts are interposed in between.

[0027] Unless otherwise defined, all terms used herein, including technical and scientific terms, have the same meaning as generally understood by those skilled in the art to which this invention pertains. Terms defined in commonly used dictionaries are further interpreted to have meanings consistent with relevant technical literature and the present disclosure, and are not interpreted in an ideal or highly formal sense unless otherwise defined.

[0028] In this specification, the term “combination(s) of these” described in the Markush-type expression means one or more mixtures or combinations selected from the group consisting of the components described in the Markush-type expression, and means including any one or more selected from the group consisting of said components.

[0029] In this specification, "secondary particle" means an aggregate, i.e., a secondary structure, formed by the aggregation of tens to hundreds of primary particles by physical or chemical bonding between primary particles without an intentional aggregation or assembly process of the primary particles.

[0030] "Primary particle" refers to the smallest particle unit that is distinguished as a single mass when the cross-section of the positive active material precursor or positive active material is observed through a scanning electron microscope (SEM), and may consist of a single crystal grain or multiple crystal grains.

[0031] In this specification, "grain" refers to a distinct region in which atoms within a primary particle form a lattice structure in a certain direction.

[0032] Hereinafter, embodiments of the present invention are described in detail so that those skilled in the art can easily implement the invention. However, the present invention may be embodied in various different forms and is not limited to the embodiments described herein.

[0033] <Cathode active material precursor for lithium secondary batteries>

[0034] A positive electrode active material precursor according to one aspect of the present invention comprises a transition metal precursor that includes nickel and manganese but does not include cobalt.

[0035] The above transition metal precursor may be secondary particles formed by the aggregation of primary particles.

[0036] The above transition metal precursor includes pores having a bimodal distribution in which two peaks appear at pore diameters in the range of 1 nm to 20 nm in the pore size distribution graph obtained through the BJH (Barrett-Joyner-Halenda) method.

[0037] In the above pore size distribution graph, one peak may be located at a pore diameter of less than 10 nm, and another peak may be located at a pore diameter greater than 10 nm.

[0038] In this way, pores of different diameters of less than 20 nm can be evenly distributed in the positive active material precursor according to an embodiment of the present invention.

[0039] The pore volume of the transition metal precursor calculated from the pore size distribution graph above is 0.1 cm 3 / g to 0.12 cm 3 It can be / g.

[0040] In this way, by evenly distributing pores of different diameters of less than 20 nm in the positive active material precursor, the positive active material precursor according to the embodiment of the present invention can have a high pore volume.

[0041] The above transition metal precursor may include NiMnO3 and Mn2O3.

[0042] In the XDR pattern of the above transition metal oxide, the full width at half maximum (FWHM) of the XRD peak (2θ = 41° to 43°) for the (113) crystal plane of NiMnO3 may be in the range of 1.2° to 1.6°.

[0043] As such, the positive active material precursor according to an embodiment of the present invention may include a transition metal precursor in the form of an oxide.

[0044] The positive electrode active material precursor according to an embodiment of the present invention may include a transition metal precursor in the form of an oxide. The positive electrode active material precursor according to an embodiment of the present invention may further include a trace amount of a transition metal precursor in the form of a hydroxide.

[0045] The above transition metal precursor may have a manganese content greater than the nickel content.

[0046] The above transition metal precursor may contain 55 mol% to 80 mol% of manganese among the total transition metals, and preferably 55 mol% to 75 mol%.

[0047] The above transition metal precursor is 35 m 2 / g to 42 m 2 / It can have a BET specific surface area of ​​g.

[0048] The positive active material precursor containing nickel and manganese and not containing cobalt according to an embodiment of the present invention has pores with a pore diameter of 20 nm or less having a bimodal distribution and has a high pore volume, thereby improving the room temperature discharge capacity of the positive active material for a lithium secondary battery.

[0049] Method for manufacturing a cathode active material precursor for lithium secondary batteries

[0050] A method for manufacturing a positive electrode active material precursor for a lithium secondary battery according to one aspect of the present invention comprises the step of manufacturing a transition metal precursor containing nickel and manganese and not containing cobalt.

[0051] A co-precipitation reaction can be performed by introducing a nickel-containing raw material, a manganese-containing raw material, a chelating agent such as an aqueous ammonia solution, and an aqueous alkaline solution for pH adjustment into a co-precipitation reactor.

[0052] The above nickel-containing raw material is not particularly limited as long as it is used in the manufacture of a cathode active material precursor in the relevant technical field. As a non-limiting example, the above nickel-containing raw material may be a nickel-containing sulfate, acetate, nitrate, halide, sulfide, hydroxide, oxide, or oxyhydroxide, and specifically, may be NiSO4, NiSO4·6H2O, Ni(OH)2, NiO, NiOOH, NiCO3·2Ni(OH)2·4H2O, NiC2O2·2H2O, Ni(NO3)2·6H2O, nickel fatty acid salt, nickel halide, or a combination thereof.

[0053] The above manganese-containing raw material may be, as a non-limiting example, a manganese-containing sulfate, acetate, nitrate, halide, sulfide, hydroxide, oxide, oxyhydroxide, or a combination thereof, and specifically, may be a manganese salt such as MnSO4, MnCO3, Mn(NO3)2, manganese acetate, manganese dicarboxylate, manganese citrate, and manganese fatty acid, manganese oxide such as Mn2O3, MnO2, and Mn3O4, manganese oxyhydroxide, manganese chloride, or a combination thereof.

[0054] The above ammonia solution may include, as a complex-forming agent, NH3, NH4OH, (NH4)2SO4, NH4NO3, NH4Cl, CH3COONH4, NH4CO3, or combinations thereof, as non-limiting examples. Meanwhile, the above ammonia solution may be used in the form of an aqueous solution, wherein water or a mixture of water and an organic solvent that is uniformly miscible with water, such as alcohol, may be used as the solvent.

[0055] The above pH adjuster may be a caustic soda solution and may include an alkali compound of an alkali metal or alkaline earth metal such as NaOH, KOH, or Ca(OH)2, a hydrate thereof, or a combination thereof. The above caustic soda solution may also be used in the form of an aqueous solution, wherein water or a mixture of water and an organic solvent such as an alcohol that is uniformly miscible with water may be used as the solvent.

[0056] The above co-precipitation reaction may be carried out under an inert atmosphere, such as nitrogen or argon, to prevent oxidation of metal ions. Specifically, the above co-precipitation reaction may be carried out while injecting nitrogen.

[0057] The above co-precipitation reaction can be performed at a temperature within the reactor of 30°C to 70°C, specifically 40°C to 60°C, and more specifically 45°C to 55°C. By performing the co-precipitation reaction within the above temperature range, particles of nickel-manganese elemental hydroxide can be generated and precipitated in the reaction solution. The precipitated precursor particles can be separated and dried according to conventional methods to obtain a transition metal precursor in the form of a hydroxide containing nickel and manganese. The transition metal precursor may be a secondary particle formed by the aggregation of primary particles.

[0058] At this time, by adjusting the concentrations of the nickel-containing raw material and the manganese-containing raw material, a precursor can be prepared in which the nickel (Ni) content of the total transition metal content is 45 mol% or less, specifically 20 mol% to 40 mol%, more specifically 30 mol% to 40 mol%, and more specifically 35 mol%. That is, the nickel content of the transition metal precursor may be 40 mol% or less based on the total molar amount of the transition metal, specifically 20 mol% to 40 mol%, more specifically 30 mol% to 40 mol%, and more specifically 35 mol%.

[0059] In one embodiment, the composition of the transition metal precursor in the form of a hydroxide containing nickel and manganese can be represented by the following chemical formula 1.

[0060] <Chemical Formula 1>

[0061] Ni x1 Mn y1 (OH)2

[0062] In the above chemical formula 1, 0.1≤x1≤0.45 and 0.55≤y1≤0.9.

[0063] As shown in Chemical Formula 1 above, by not including cobalt, the structural stability is improved and there is an advantage of excellent electrochemical properties by substituting manganese for cobalt in existing NCM-based precursors.

[0064] In addition, a method for manufacturing a positive electrode active material precursor for a lithium secondary battery according to one embodiment of the present invention includes the step of heat-treating the transition metal precursor at 350°C to 450°C for 3 to 7 hours. The heat-treating step may be performed in an air atmosphere in which the carbon dioxide content is in the range of 0.01 to 100 weight ppm.

[0065] The transition metal hydroxide containing nickel and manganese can be phase-transformed into a transition metal oxide by the above heat treatment.

[0066] The heat-treated transition metal precursor may include NiMnO3 and Mn2O3.

[0067] In the XRD pattern of the above transition metal oxide, the full width at half maximum (FWHM) of the XRD peak (2θ = 41° to 43°) for the (113) crystal plane of NiMnO3 may be in the range of 1.2° to 1.6°.

[0068] As such, the positive active material precursor prepared according to an embodiment of the present invention may include a transition metal precursor in the form of an oxide.

[0069] The positive electrode active material precursor prepared according to an embodiment of the present invention may include most of the transition metal precursors in the form of oxides and trace amounts of transition metal precursors in the form of hydroxides.

[0070] And, the heat-treated transition metal precursor is a secondary particle formed by the aggregation of primary particles, and the heat-treated transition metal precursor includes pores having a bimodal distribution in pore diameters ranging from 0.1 nm to 20 nm in a pore size distribution graph obtained through the BJH (Barrett-Joyner-Halenda) method.

[0071] In the above pore size distribution graph, one peak may be located at a pore diameter of less than 10 nm, and another peak may be located at a pore diameter greater than 10 nm.

[0072] In this way, pores of different diameters of less than 20 nm can be evenly distributed in the positive active material precursor prepared according to an embodiment of the present invention.

[0073] The pore volume of the transition metal precursor calculated from the pore size distribution graph above is 0.1 cm 3 / g to 0.12 cm 3 It can be / g.

[0074] In this way, according to an embodiment of the present invention, the method for manufacturing a positive active material precursor allows pores of different diameters of less than 20 nm to be evenly distributed in the positive active material precursor, thereby enabling the positive active material precursor manufactured according to an embodiment of the present invention to have a high pore volume.

[0075] The heat-treated transition metal precursor may contain 55 mol% to 80 mol% of manganese among the total transition metals, and preferably 55 mol% to 75 mol%.

[0076] The method for manufacturing a positive electrode active material precursor for a lithium secondary battery according to the present invention can improve the room temperature discharge capacity of the positive electrode active material for a lithium secondary battery by having a positive electrode active material precursor containing nickel and manganese and not containing cobalt, having pores with a pore diameter of 20 nm or less that have a bimodal distribution and a high pore volume.

[0078] Cathode active material for lithium secondary batteries

[0079] The positive electrode active material for a lithium secondary battery according to an embodiment of the present invention may include a lithium nickel manganese oxide that includes nickel (Ni) and manganese (Mn) and does not include cobalt (Co).

[0080] The above lithium nickel manganese oxide may contain 55 mol% or more of manganese (Mn) among the total metals excluding lithium (Li), specifically 60 mol% to 80 mol%, more specifically 60 mol% to 70 mol%, and even more specifically 65 mol%.

[0081] The above lithium nickel manganese oxide may contain nickel (Ni) in an amount of 45 mol% or less among the total metals excluding lithium (Li), specifically 20 mol% to 40 mol%, more specifically 30 mol% to 40 mol%, and even more specifically 35 mol%.

[0082] In one embodiment of the present invention, the positive electrode active material for a lithium secondary battery may have a molar ratio of lithium (Li / Me) to the total metal (Me) excluding lithium (Li) of 1 to 1.5, specifically 1.1 to 1.4, and more specifically 1.29 to 1.35.

[0083] In one embodiment of the present invention, a positive electrode active material for a lithium secondary battery can be represented by the following chemical formula 2.

[0084] [Chemical Formula 2]

[0085] Li a Ni x Mn y O2

[0086] In the above chemical formula 2, 1≤a≤1.5, 0.1≤x≤0.45, and 0.55≤y≤0.9.

[0088] In one embodiment of the present invention, the positive electrode active material for a lithium secondary battery may have a crystallite size of 50 nm to 54 nm.

[0089] In this specification, "crystallite" refers to at least one crystal growth unit in a crystalline material, and "crystallite size" can be estimated using peak broadening of XRD data and can be quantitatively calculated through the Scherrer equation.

[0090] In one embodiment of the present invention, the positive electrode active material for a lithium secondary battery may be a secondary particle formed by the aggregation of primary particles, and the central particle diameter (D50) of the secondary particle may be 10㎛ to 11㎛.

[0091] By controlling the central particle size (D50) of the positive electrode active material to the above range, the electrode electrolyte and active area can be reduced, thereby improving electrochemical safety. In this specification, the central particle size (D50) can be defined as the particle size corresponding to 50% of the cumulative volume in the particle size distribution curve. The central particle size (D50) can be measured, for example, using a particle size distribution meter that utilizes a laser diffraction method.

[0093] Hereinafter, a method for manufacturing a positive electrode active material for a lithium secondary battery according to the present invention will be described. The present invention is not necessarily limited to the method for manufacturing a positive electrode active material described below, and may be manufactured according to a method for manufacturing a positive electrode active material well known in the art.

[0094] Method for manufacturing a positive electrode active material for a lithium secondary battery

[0095] A method for manufacturing a positive electrode active material for a lithium secondary battery according to the present invention includes the step of mixing the aforementioned positive electrode active material precursor and a lithium raw material to obtain a lithium transition metal oxide that does not contain cobalt.

[0096] A step is performed to form a mixture containing the heat-treated transition metal precursor and lithium raw material, and then calcinate to form a lithium transition metal oxide.

[0097] The above lithium raw material may include, for example, Li2CO3, LiOH, or a combination thereof.

[0098] The mixing ratio of the heat-treated transition metal precursor and the lithium raw material can be adjusted according to the composition of the target lithium cathode active material.

[0099] The calcination temperature of the above mixture may be 700°C to 900°C, specifically 800°C to 900°C, more specifically 840°C to 880°C. If the calcination temperature deviates from the upper limit of the aforementioned range, the structural stability of the positive electrode active material may be reduced, and the reversible capacity may be reduced. If the calcination temperature deviates from the lower limit of the aforementioned range, there is a problem in that the particle size growth of the positive electrode active material is not sufficiently accompanied.

[0100] The above calcination time may be performed for 4 to 20 hours, specifically 8 to 12 hours. The above calcination time refers to the time maintained at the calcination temperature excluding the heating and cooling times. If the above calcination time is excessively long, there are problems regarding productivity and economic efficiency, and if the above calcination time is excessively short, there are problems in that the synthesis reaction is not fully carried out or the crystal structure is not sufficiently developed.

[0101] The obtained lithium transition metal oxide may contain 55 mol% to 90 mol% of manganese among the total metals excluding lithium, and the molar ratio of lithium (Li) to the total metals excluding lithium (Li) (Li / Me) may be 1.29 to 1.35.

[0103] <Polar>

[0104] The present invention provides a positive electrode comprising a current collector and a positive electrode active material layer located on at least one surface of the current collector.

[0105] The above current collector may be, for example, made of stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel with a surface treated with carbon, nickel, titanium, silver, etc.

[0106] Meanwhile, the above positive active material layer may include a binder and a conductive material.

[0107] At this time, the binder serves to improve adhesion between positive active material particles and adhesion between the positive active material and the positive current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethylcellulose (CMC), starch, hydroxypropylcellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one of these alone or a mixture of two or more may be used, but is not limited thereto. The binder may be included in an amount of 1% to 30% by weight relative to the total weight of the positive active material layer.

[0108] In addition, the conductive material is used to impart conductivity to the electrode, and in the battery being constructed, it may be used without special limitations as long as it possesses electronic conductivity without causing chemical changes. Specific examples include graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and one of these alone or a mixture of two or more may be used, but is not limited thereto. The conductive material may typically be included in an amount of 1% to 30% by weight relative to the total weight of the positive electrode active material layer.

[0109] The above-mentioned anode can be manufactured according to a conventional anode manufacturing method, except for using the aforementioned anode active material.

[0110] Specifically, the anode can be manufactured by applying a composition for forming an anode active material layer, comprising the aforementioned anode active material and optionally a binder, conductive material, or solvent as needed, onto an anode current collector, followed by drying and rolling. At this time, the types and contents of the anode active material, binder, and conductive material are as described above.

[0111] The above solvent may be a solvent commonly used in the relevant technical field, such as dimethylsulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and one of these alone or a mixture of two or more may be used. The amount of the above solvent used is sufficient if it has a viscosity that dissolves or disperses the anode active material, conductive material, and binder, taking into account the coating thickness of the slurry and the manufacturing yield, and subsequently provides excellent thickness uniformity when coated for anode manufacturing.

[0112] Alternatively, the anode may be manufactured by casting the composition for forming the anode active material layer onto a separate support and then laminating the film obtained by peeling off from the support onto the anode current collector.

[0113] The present invention does not limit the structure and manufacturing method of the anode.

[0115] Lithium secondary battery

[0116] The present invention provides a lithium secondary battery comprising the above-described positive electrode. A lithium secondary battery comprising the above-described positive electrode active material may have an improved room temperature discharge capacity.

[0117] The above lithium secondary battery may specifically include a positive electrode, a negative electrode positioned opposite to the positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, wherein the positive electrode is as described above. Additionally, the lithium secondary battery may optionally further include a battery container housing an electrode assembly comprising the positive electrode, the negative electrode, and the separator, and a sealing member for sealing the battery container.

[0118] In the above lithium secondary battery, the negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0119] The above-mentioned negative current collector is not particularly limited as long as it has high conductivity without causing chemical changes in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., and aluminum-cadmium alloy may be used. In addition, the above-mentioned negative current collector may typically have a thickness of 3 to 500 μm, and, similar to the positive current collector, fine irregularities may be formed on the surface of the current collector to strengthen the bonding strength of the negative active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0120] The above-mentioned cathode active material layer may optionally include a binder and a conductive material together with the cathode active material. The above-mentioned cathode active material layer may be manufactured, as an example, by applying a composition for forming a cathode active material layer, comprising a cathode active material and optionally a binder and a conductive material, onto a cathode current collector and drying it, or by casting the composition for forming a cathode onto a separate support and then laminating the film obtained by peeling it off from the support onto a cathode current collector.

[0121] As the above-mentioned negative electrode active material, a compound capable of reversible intercalation and deintercalation of lithium may be used. Specific examples include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, or Al alloys; metal oxides capable of doping and dedoping lithium, such as SiOβ (0 < β < 2), SnO2, vanadium oxide, and lithium vanadium oxide; or composites comprising the above-mentioned metallic compounds and carbonaceous materials, such as Si-C composites or Sn-C composites, and any one or more of these may be used. Additionally, a metallic lithium thin film may be used as the above-mentioned negative electrode active material. Furthermore, the carbon material may include both low-crystallinity carbon and high-crystallinity carbon. Representative examples of low-crystallinity carbon include soft carbon and hard carbon, while representative examples of high-crystallinity carbon include amorphous, plate-like, flake-like, spherical, or fibrous natural or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch-based carbon fiber, meso-carbon microbeads, mesophase pitches, and high-temperature calcined carbon such as petroleum or coal tar pitch-derived cokes.

[0122] The binder and conductive material mentioned above may be the same as those previously described in the anode.

[0123] Next, depending on the type of lithium secondary battery, a separator may be present between the positive and negative electrodes. As such a separator, polyethylene, polypropylene, polyvinylidene fluoride, or a multilayer film of two or more layers thereof may be used, and a mixed multilayer film such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, or a polypropylene / polyethylene / polypropylene three-layer separator may also be used.

[0124] In addition, regarding the above lithium secondary battery, the electrolyte may include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, molten inorganic electrolytes, etc., which are usable when manufacturing a lithium secondary battery, but is not limited to these.

[0125] Specifically, the organic liquid electrolyte may include an organic solvent and a lithium salt. The organic solvent may be used without special limitations as long as it can serve as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent may include ester-based solvents such as methyl acetate, ethyl acetate, γ-butyrolactone, and ε-caprolactone; ether-based solvents such as dibutyl ether or tetrahydrofuran; ketone-based solvents such as cyclohexanone; and aromatic hydrocarbon-based solvents such as benzene and fluorobenzene. Carbonate-based solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), and propylene carbonate (PC); alcohol-based solvents such as ethyl alcohol and isopropyl alcohol; nitriles such as R-CN (where R is a straight-chain, branched, or cyclic hydrocarbon group having C2 to C20 structures and may include a double bond, an aromatic ring, or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolanes may be used.Among these, a carbonate-based solvent is preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate, etc.) having high ionic conductivity and high dielectric constant that can improve the charge / discharge performance of the battery, and a low-viscosity linear carbonate-based compound (e.g., ethylmethyl carbonate, dimethyl carbonate or diethyl carbonate, etc.) is more preferred. In this case, using a mixture of the cyclic carbonate and the chain carbonate in a volume ratio of about 1:1 to about 1:9 can result in excellent performance of the electrolyte.

[0126] The above lithium salt can be used without special restrictions as long as it is a compound capable of providing lithium ions used in lithium secondary batteries. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The concentration of the lithium salt is preferably used within the range of 0.1 to 2.0 M. When the concentration of the lithium salt falls within the above range, the electrolyte has appropriate conductivity and viscosity, so it can exhibit excellent electrolyte performance and allow lithium ions to move effectively.

[0127] The present invention does not limit the structure and manufacturing method of the battery.

[0129] Hereinafter, embodiments and comparative examples of the present invention will be described. However, the embodiments are presented as examples and the present invention is not limited thereto.

[0130] Examples

[0131] (1) Positive active material precursor

[0132] Ni 0.35 Mn 0.65A hydroxide precursor of (OH)2 composition was introduced into a calcination furnace with a moisture-removed air atmosphere, and then heated to 400°C for 5 hours to produce a cathode active material precursor. The air atmosphere inside the calcination furnace was formed by injecting CFA (Carbon dioxide Free Air), which is air having a carbon dioxide content in the range of 0.01 to 100 weight ppm.

[0133] (2) Positive active material

[0134] Next, a mixture was prepared by uniformly mixing Li2CO3 with the heat-treated cathode active material precursor. At this time, the molar ratio of lithium (Li) to the total metal (Me) excluding lithium (Li / Me) was designed to be 1.33.

[0135] Next, the above mixture was introduced into a kiln with a moisture-removed air atmosphere and heated to 860°C for 10 hours to obtain a lithium transition metal oxide.

[0136] Subsequently, a positive electrode active material containing lithium transition metal oxide was prepared by classifying using a mesh.

[0137] Comparative Example 1

[0138] Ni 0.35 Mn 0.65 A positive electrode active material precursor and a positive electrode active material were prepared in the same manner as in the above example, except that the (OH)2 composition hydroxide precursor was not heat-treated.

[0139] Comparative Example 2

[0140] Ni 0.35 Mn 0.65 A positive electrode active material precursor and a positive electrode active material were prepared in the same manner as in the above example, except that a (OH)2 composition hydroxide precursor was heat-treated at 200°C.

[0141] Comparative Example 3

[0142] Ni 0.35 Mn0.65 A positive electrode active material precursor and a positive electrode active material were prepared in the same manner as in the above example, except that a (OH)2 composition hydroxide precursor was heat-treated at 300°C.

[0143] Comparative Example 4

[0144] Ni 0.35 Mn 0.65 A positive electrode active material precursor and a positive electrode active material were prepared in the same manner as in the above example, except that a (OH)2 composition hydroxide precursor was heat-treated at 350°C.

[0145] Comparative Example 5

[0146] Ni 0.35 Mn 0.65 A positive electrode active material precursor and a positive electrode active material were prepared in the same manner as in the above example, except that a (OH)2 composition hydroxide precursor was heat-treated at 450°C.

[0147] Comparative Example 6

[0148] Ni 0.35 Mn 0.65 A positive electrode active material precursor and a positive electrode active material were prepared in the same manner as in the above example, except that a (OH)2 composition hydroxide precursor was heat-treated at 500°C.

[0150] Characterization of positive electrode active material precursors

[0151] (1) X-ray diffraction (XRD) analysis of the precursor

[0152] XRD analysis was performed on the cathode active material precursors prepared according to the examples and comparative examples. X-ray diffraction analysis was conducted using Rigaku's smart lab equipment.

[0153] The XRD measurement results of the cathode active material precursors prepared according to the examples and comparative examples are shown in Figure 1.

[0154] Referring to Figure 1, it can be seen that in the case of a positive active material precursor heat-treated at a temperature of 300°C or higher, some of the hydroxide undergoes a phase transition into an oxide. Hydroxides and oxides are mixed within the positive active material precursor heat-treated at 300°C. It can be seen that hydroxides still remain within the positive active material precursor heat-treated at 350°C. However, in the case of a positive active material precursor heat-treated at a temperature of 400°C to 500°C, it can be confirmed that most or all of the hydroxide undergoes a phase transition into an oxide. The positive active material precursor heat-treated at a temperature of 400°C to 500°C contained NiMnO3 and Mn2O3 oxides.

[0155] The full width at half maximum (FWHM) of the XRD peaks for the (113) crystal planes of NiMnO3 in the XRD patterns of the cathode active material precursors prepared according to the examples and comparative examples is shown in Table 1 below.

[0156] Heat treatment temperature (°C) Peak half-width (°) Comparative Example 1 - - Comparative Example 2 200 - Comparative Example 3 300 2.3639 Comparative Example 4 350 1.9422 Examples 400 1.4030 Comparative Example 5 450 0.9777 Comparative Example 6 500 0.6491

[0157] (2) Analysis of the specific surface area and pore volume of the precursor

[0158] Approximately 3 g of the cathode active material precursor prepared according to the examples and comparative examples was placed in a sample tube, and the sample was treated at 120°C for 2 hours in a vacuum atmosphere using a sample pretreatment device (VacPrep 061) to remove contaminants from the surface of the cathode active material precursor. Subsequently, the sample was introduced into a specific surface area and porosity analyzer (TriStar II Plus), and the adsorption-desorption isotherm curve was measured using nitrogen gas at liquid nitrogen temperature with the relative pressure set to a range of 0.01 to 0.99 P / P0. The specific surface area was calculated by the BET (Brunauer-Emmet-Teller) method. A pore size distribution graph was obtained using the BJH (Barrett-Joyner-Halenda) method, and the pore volume was calculated from the pore size distribution graph in the range of 1 to 30 nm.

[0159] The pore size distribution of the positive active material precursors prepared according to the examples and comparative examples is shown in Figure 2.

[0160] Referring to Figure 2, as the heat treatment temperature of the positive active material precursor increased, the proportion of small diameter pores decreased and the proportion of large diameter pores increased.

[0161] The cathode active material precursor prepared according to the example had a bimodal distribution in which two peaks appeared at pore diameters in the range of 1 nm to 20 nm in the pore size distribution graph (hereinafter referred to as the "BJH pore size distribution graph") obtained through the BJH (Barrett-Joyner-Halenda) method.

[0162] In the BJH pore size distribution graph of the cathode active material precursor prepared according to the example, one peak was located at a pore diameter of less than 10 nm, and another peak was located at a pore diameter greater than 10 nm. Specifically, in the BJH pore size distribution graph of the cathode active material precursor prepared according to the example, one peak was located at a pore diameter of about 7 nm to 8 nm, and another peak was located at a pore diameter of about 12 nm to 13 nm.

[0163] On the other hand, in the BJH pore size distribution graphs of the cathode active material precursors prepared according to Comparative Example 1 and Comparative Example 2, a single peak was identified at a pore diameter of about 4 nm to 6 nm. Also, in the BJH pore size distribution graph of the cathode active material precursor according to Comparative Example 3, a somewhat broadened single peak was identified at a pore diameter in the range of about 4 nm to 8 nm. Furthermore, in the BJH pore size distribution graph of the cathode active material precursor according to Comparative Example 5, pores with a pore diameter of 10 nm or less were mostly removed, and a broad single peak was identified with a peak at a pore diameter of about 25 nm or more.

[0164] The specific surface area and pore volume of the cathode active material precursors prepared according to the examples and comparative examples are shown in Table 2 below.

[0165] Heat treatment temperature (°C) Specific surface area (m²) 2 / g) Pore ​​volume (cm²) 3 / g) Comparative Example 1 - 28.82 0.0556 Comparative Example 2 200 30.05 0.0634 Comparative Example 3 300 43.48 0.1013 Comparative Example 4 350 52.33 0.1109 Examples 400 40.87 0.1176 Comparative Example 5 450 33.63 0.1106 Comparative Example 6 500 18.25 0.0725

[0166] Referring to Figure 2 and Table 2, it can be seen that the cathode active material precursor according to the example has small diameter pores of less than 10 nm and large diameter pores of more than 10 nm mixed in similar proportions, and has the largest pore volume compared to the comparative examples.

[0168] Characterization of positive electrode active materials

[0169] (1) Particle size analysis

[0170] The particle size distribution of the cathode active materials prepared according to the examples and comparative examples was measured using a Microtrac S3000 instrument utilizing the laser diffraction method. The D50 values ​​of the cathode active materials prepared according to the examples and comparative examples are listed in Table 3 below.

[0171] (2) Evaluation of crystallite size

[0172] The grain size of the cathode active materials prepared according to the examples and comparative examples was quantitatively calculated using XRD data and the Scherrer equation and is shown in Table 3. XRD data of the cathode active materials prepared according to the examples and comparative examples were measured using Rigaku’s smart lab equipment. The XRD peak used in the calculation is the peak of the (104) crystal plane. The grain size values ​​of the cathode active materials prepared according to the examples and comparative examples are listed in Table 3 below.

[0173] (3) Evaluation of cation mixing ratio

[0174] For the cathode active materials prepared according to the examples and comparative examples, the cation mixing ratio was measured by dividing the intensity of the (003) crystal plane peak of the XRD data by the intensity of the (104) crystal plane peak. Table 3 below shows the I of the cathode active materials prepared according to the examples and comparative examples. 003 / I 104 The value was written.

[0175] (4) Tap density evaluation

[0176] 10 g of positive active material was placed in a cylinder with a diameter of 19.1 mm, a pressure of 108 N was applied, and the height of the cylinder was measured to evaluate the tap density. The tap densities of the positive active materials prepared according to the examples and comparative examples are shown in Table 3 below. The value was written.

[0177] Dmin(μm) D50(μm) Dmax(μm) Grain size (nm) Cation mixture (I 003 / I 104 ) Tap density (g / cc) Comparative Example 1 7.28 11.12 22.33 51.4 1.64 2.12 Comparative Example 2 7.25 10.99 21.15 53.36 1.60 2.04 Comparative Example 3 7.26 11.60 26.71 48.10 1.67 2.00 Comparative Example 4 7.23 11.18 23.70 50.54 1.63 1.96 Examples 7.26 10.94 21.00 52.01 1.58 2.11 Comparative Example 5 7.24 10.86 20.68 56.55 1.58 2.12 Comparative Example 6 7.21 10.73 20.29 57.53 1.58 2.21

[0178] (5) Lithium secondary battery performance evaluation

[0179] To evaluate the electrochemical properties of the positive electrode active materials prepared according to the examples and comparative examples, a coin-type half-cell CR2032 coin cell was prepared as follows.

[0180] Specifically, a positive electrode active material, a conductive material (acetylene black FX35, Denka), and a polyvinylidene fluoride (PVDF) binder (product name: KF9709) were mixed in a weight ratio of 92.5:3.5:4.0, and this mixture was added to an N-methyl-2-pyrrolidone solvent so that the solid content was about 59 to 63 weight% to prepare a positive electrode active material slurry.

[0181] The above slurry was coated onto an aluminum foil (Al foil, thickness: 20 μm), which serves as an anode current collector, using a doctor blade, and an anode was manufactured by drying and rolling. The loading amount of the anode was approximately 14-15 mg / cm², and the rolling density was approximately 2.75 g / cm³. 3 It was.

[0182] A 2032 coin-type half-cell was manufactured by a conventional method using the above-mentioned positive electrode, lithium metal negative electrode (thickness 400 μm, NEBA), electrolyte, and polypropylene polyethylene separator. The above-mentioned electrolyte was prepared by dissolving 1M LiPF6 in a mixed solvent of ethylene carbonate, dimethyl carbonate, and diethyl carbonate (mixing ratio EC:DMC:DEC = 1:2:1 volume%) to prepare a mixed solution, and then adding 3 weight% of vinylene carbonate (VC) to it.

[0183] After aging the coin-type half-cell at high temperature (HT, 45℃) for 10 hours, a reference capacity of 200 mAh / g was set for the initial capacity evaluation, and charge / discharge conditions of CC / CV 2.0~4.65V and 0.05 cut-off were applied. The initial capacity was measured by charging at 0.1C / discharging at high temperature (45℃).

[0184] In addition, for room temperature capacity evaluation, measurements were taken at room temperature (RT, 25℃) with a CC / CV of 2.5V to 4.4V and a 0.05C cut-off applied, using 0.1C / charge and 0.1C / discharge.

[0185] Meanwhile, to measure the output characteristics (rate characteristics), charge and discharge tests were performed at 0.1C and 0.33C with a CC / CV of 2.5~4.4V and a 0.05C cut-off applied at room temperature, and the ratio of the 0.33C discharge capacity to the 0.1C discharge capacity (rate characteristics, %) is shown in Table 4 below.

[0186] High temperature charge / discharge test Room temperature charge / discharge test 0.1C charging (mAh / g) 0.1C discharge (mAh / g) Efficiency (%) 0.1C discharge (mAh / g) 0.33C discharge (mAh / g) Rate characteristics (%) Comparative Example 1 294.8 276.5 93.8 216.6 200.9 92.8 Comparative Example 2 290.7 273.6 94.1 216.7 202.8 93.6 Comparative Example 3 292.4 274.2 92.6 217.3 201.6 93.4 Comparative Example 4 295.5 274.6 92.9 217.3 200.6 92.3 Examples 295.0 276.1 93.6 219.1 203.6 92.9 Comparative Example 5 293.2 274.0 93.5 217.4 202.6 93.2 Comparative Example 6 289.3 271.2 93.0 215.0 200.0 93.0

[0187] Referring to Table 4, it can be seen that when applied to a lithium secondary battery, the electrochemical characteristics of the positive electrode active material according to the example, particularly the room temperature discharge capacity, are superior to those of the comparative examples.

[0189] The present invention is not limited to the above embodiments and can be manufactured in various different forms, and those skilled in the art will understand that the invention can be implemented in other specific forms without changing the technical concept or essential features of the invention. Therefore, the embodiments described above should be understood as illustrative in all respects and not restrictive.

Claims

Claim 1 A positive electrode active material precursor comprising a transition metal precursor comprising nickel and manganese but not cobalt, wherein the transition metal precursor comprises secondary particles formed by the aggregation of primary particles, and wherein the transition metal precursor comprises pores having a bimodal distribution in which two peaks appear at pore diameters in the range of 1 nm to 20 nm in a pore size distribution graph obtained through the BJH (Barrett-Joyner-Halenda) method. Claim 2 A positive active material precursor according to claim 1, wherein in the pore size distribution graph, one peak is located at a pore diameter of less than 10 nm and the other peak is located at a pore diameter greater than 10 nm. Claim 3 In claim 1, the pore volume of the transition metal precursor calculated from the pore size distribution graph is 0.1 cm 3 / g to 0.12 cm 3 / g positive active material precursor. Claim 4 In claim 1, the above transition metal precursor is a positive active material precursor comprising NiMnO3. Claim 5 In claim 4, the positive active material precursor, wherein the full width at half maximum (FWHM) of the XRD peak for the (113) crystal plane of NiMnO3 in the XRD pattern of the transition metal precursor is in the range of 1.2° to 1.6°. Claim 6 A positive electrode active material precursor according to claim 1, wherein the transition metal precursor comprises 55 mol% to 80 mol% of manganese among the total transition metals. Claim 7 In claim 1, the transition metal precursor is 35 m 2 / g to 42 m 2 / A positive electrode active material precursor having a BET specific surface area of ​​g. Claim 8 A method for manufacturing a positive electrode active material precursor, comprising the steps of: preparing a transition metal precursor that does not contain cobalt by co-precipitating nickel raw material and manganese raw material; and heat-treating the transition metal precursor at 350°C to 450°C for 3 to 7 hours, wherein the heat-treating step is performed in an air atmosphere having a carbon dioxide content in the range of 0.01 to 100 weight ppm. Claim 9 A method for manufacturing an anode active material precursor, wherein, in claim 8, the heat-treated transition metal precursor comprises secondary particles formed by the aggregation of primary particles, and the heat-treated transition metal precursor has a bimodal distribution in a pore diameter range of 0.1 nm to 20 nm in a pore size distribution graph obtained through the BJH (Barrett-Joyner-Halenda) method. Claim 10 In claim 9, the pore volume of the transition metal precursor calculated from the pore size distribution graph is 0.1 cm 3 / g to 0.12 cm 3 Method for manufacturing a positive electrode active material precursor, with a g / g. Claim 11 A method for manufacturing an anode active material precursor, wherein the heat-treated transition metal precursor comprises NiMnO3 in claim 9. Claim 12 A method for manufacturing an anode active material precursor according to claim 11, wherein the full width at half maximum (FWHM) of the peak for the (113) crystal plane of NiMnO3 in the XRD pattern of the heat-treated transition metal precursor (2θ = 41° to 43°) is in the range of 1.2° to 1.6°. Claim 13 A method for manufacturing an anode active material precursor according to claim 9, wherein the transition metal precursor comprises 55 mol% to 80 mol% of manganese among the total transition metals: Claim 14 In claim 9, the heat-treated transition metal precursor is 35 m 2 / g to 42 m 2 / Method for preparing a positive electrode active material precursor having a BET specific surface area of ​​g.

Citation Information

Patent Citations

  • Mix active material for lithium secondary battery, electrode for lithium secondary battery, and lithium secondary battery

    JP2015026594A

  • Method for preparing positive electrode active material precursor, positive electrode active material precursor and method for preparing positive electrode active material by using the positive electrode active material precursor

    KR1020240097733A